IKRAR JATUKRAMI: IKRAR PERNIKAHAN KONTEKS SUNDA - Neng Eri Sofiana (IAIN Manado, 2019)
Abstract: Generally, marriage contract is a statement from the female guardian and acceptance from the bridegroom, but it is different from the Jatukrami pledge made by the Sunda Wiwitan indigenous people which begins with the statement of the bride and then responds by the guardian. The practice is done by uniting the thumbs of the bride's right hand and closing with the guardian's right hand fist. Most are done after the marriage contract in KUA, but in other cases it is carried out independently. Then what is the f urf review of the implementation and existence of the Jatukrami pledge on the Sunda Wiwitan indigenous people? The pledge of jatukrami as a mechanism for marriage pledges using Sundanese, begins with an introduction delivered by pangjejer and several questions submitted to the bride and groom, followed by a request for a marriage permit from the bride to the guardian (father) answered by giving permission from the guardian and being greeted with thanksgiving from both brides and endorsed by indigenous elders. This form of pledge is justified f urf and includes al-‘urf as-s ah which can be maintained and maintained. The reason for its existence is divided into three parts, namely the people who consider it as custom, so that the marriage contract is still carried out. Then the people who consider it as a mandatory instrument in marriage, so that they feel enough with the jatukrami pledge, and the people who assume that marriage is legal with a contract in KUA, so they do not carry out jatukrami pledges.Keyword: Ikrar Jatukrami, Sunda Wiwitan, Marriege. Abstrak: Umumnya, akad nikah ialah pernyataan dari wali perempuan dan penerimaan dari mempelai pria, namun berbeda dengan ikrar Jatukrami yang dilakukan oleh masyarakat adat Sunda Wiwitan yang diawali dengan pernyataan mempelai wanita kemudian ditanggapi wali. Praktiknya dilakukan dengan menyatukan jempol tangan kanan mempelai dan ditutup dengan kepalan tangan kanan wali perempuan. Kebanyakan dilakukan setelah akad nikah di KUA, namun dalam kasus lain dilakukan mandiri. Lalu bagaimana tinjauan ‘urf terhadap pelaksanaan dan eksistensi ikrar Jatukrami pada masyarakat adat Sunda Wiwitan? Ikrar jatukrami sebagai mekanisme ikrar pernikahan dengan menggunakan bahasa Sunda, diawali dengan pengantar yang disampaikan oleh pangjejer dan beberapa pertanyaan yang diajukan kepada kedua mempelai, dilanjutkan dengan permintaan izin menikah dari mempelai wanita kepada wali (ayah) yang dijawab dengan pemberian izin dari wali dan disambut dengan ucapan syukur dari kedua mempelai dan disahkan oleh sesepuh adat. Bentuk ikrar ini dibenarkan secara ‘urf dan termasuk al-‘urf as-sahih yang dapat dipertahankan dan dipelihara. Adapun alasan eksistensinya terbagi menjadi tiga bagian, yakni masyarakat yang mengganggap sebagai adat, sehingga akad nikah tetap dilakukan. Kemudian masyarakat yang mengganggapnya sebagai instrumen wajib dalam pernikahan, sehingga merasa cukup dengan ikrar jatukrami saja, dan masyarakat yang mengganggap bahwa pernikahan sudah sah dengan akad di KUA, sehingga tidak melaksanakan ikrar jatukrami.Kata kunci: Ikrar Jatukrami, Sunda Wiwitan, Akad Nikah.